Visible light activated photocatalytic behaviour of rare earth modified commercial TiO2 - Tobaldi, D. M.
A commercial TiO2 nanopowder, Degussa P25, was modified with several rare earth (RE) elements in order to extend its photocatalytic activity into the visible range. The mixtures were prepared via solid-state reaction of the precursor oxides, and thermally treated at high temperature (900 and 1000 degrees C), with the aim of investigating the photocatalytic activity of the thermally treated samples. This thermal treatment was chosen for a prospective application as a surface layer in materials that need to be processed at high temperatures. The photocatalytic activity (PCA) of the samples was assessed in gas-solid phase - monitoring the degradation of isopropanol (IPA) - under visible-light irradiation. Results showed that the addition of the REs lanthanum, europium and yttrium to TiO2 greatly improved its photocatalytic activity, despite the thermal treatment, because of the presence of more surface hydroxyl groups attached to the photocatalyst's surface, together with a higher specific surface area (SSA) of the modified and thermally treated samples, with regard to the unmodified and thermally treated Degussa P25. The samples doped with La, Eu and Y all had excellent PCA under visible-light irradiation, even higher than the untreated Degussa P25 reference sample, despite their thermal treatment at 900 degrees C, with lanthanum producing the best results (i.e. the La-, Eu- and Y-TiO2 samples, thermally treated at 900 degrees C, had, respectively, a PCA equal to 26, 27 and 18 ppm h(-1) - in terms of acetone formation - versus 15 ppm h(-1) for the 900 degrees C thermally treated Degussa P25). On the other hand, Ce-TiO(2)s had no significant photocatalytic activity. (C) 2013 Elsevier Ltd. All rights reserved.